UHPLC Analysis of Polyphenol Composition and Antioxidant Activity from Different Solvent Extracts of Coriandrum sativum Seeds Cultivated in Korea - Nagella, Praveen; Thiruvengadam, Muthu; Ahmad, Ateeque; Chung, Ill-Min (Asian Journal of Chemistry, 2014)
The aim of this work was to establish the polyphenolic profile and antioxidant capacity of Coriandrum sativum seeds that could potentially be used in the human diet. An ultra high performance liquid chromatographic method was used to identify and quantify individual phenolic compounds of the C. sativum seeds. A total of 24 polyphenolic compounds were identified and quantified in C. sativum seeds, including hydroxybenzoic acids, hydroxycinnamic acids, flavonols and other groups of phenolic compounds. Ultra high performance liquid chromatographic analysis of the seed extract revealed that salicylic acid was the dominant phenolic compound in coriander seed extract, it constituted about 650.80 μg/g, followed by gentisic acid (223.45 μg/g), chlorogenic acid (162.10 μg/g), pyrogallol (138.80 μg/g) and syringic acid (90.95 μg/g). The C. sativum seeds was extracted with 4 different solvents (ethyl acetate, methanol, butanol and water) and screened for total phenolic content, total flavonoid content and antioxidant activity. The antioxidant activity of C. sativum seeds was assessed by evaluating the 1,1-diphenyl-2-picrylhydrazyl (DPPH), reducing power, metal chelating and phosphomolybdenum assay. Ethyl acetate extract exhibited the highest phenolic (23.09 mg/g gallic acid equivalent) and flavonoid contents (1.08 mg/g quercetin equivalent). The ethyl acetate extract possesses highest antioxidant activity towards DPPH, reducing power, metal chelating and phosphomolybdenum assay. The antioxidant activity among the C. sativum seed extracts assayed through all the four methods was found to be ethyl acetate > butanol > methanol > water extract. In conclusion, addition of coriander seeds to food increases the antioxidant content and may have potential as a natural antioxidant and thus inhibit undesired oxidation processes.